The coaching process in football - A qualitative perspective - Sarmento, H.; Pereira, A.; Anguera, M. T.; Campanico, J.; Leitao, J. (Montenegrin Journal of Sports Science and Medicine, 2014)
This study aims to understand what the coaches observe in the game, and how they evaluate and make their intervention based on this observation. The participants were 8 experienced First Portuguese League coaches. Semi-structured interviews were carried out and the data were analysed through the technique of content analysis. The software QSR NVivo 9 was used in coding the transcripts of the interviews. According to these coaches to effectively observe and analyze the game it is crucial to have a detailed knowledge of the game and of the individual characteristics of players. They consider that the most important aspects to observe in the game are: i) the 4 moments of the game; ii) set pieces; iv) individual characteristics of players; v) random aspects of the game. Coaches have the perception that over the years their observation has become more effective and they value different aspects in the game. They consider that the factors responsible for the evolution of their observations are: i) the accumulated experience; ii) a better knowledge of the game; iii) the academic formation. These coaches evaluate the teams in a general way focusing mainly on strengths and weaknesses and they follow a specific logic of prioritization for the evaluation of these aspects that is based mainly, in their model of the game. The intervention is done mainly through the adaptation of the training exercises, but also through visual strategies (movies, photos, etc.) and meetings (individual, by sector or in group).